Resonating delay equation. (1st January 2022) - Ohira, K.
Abstract: We propose here a delay differential equation that exhibits a new type of resonating oscillatory dynamics. The oscillatory transient dynamics appear and disappear as the delay is increased between zero to asymptotically large delay. The optimal height of the power spectrum of the dynamical trajectory is observed with the suitably tuned delay. This resonant behavior contrasts itself against the general behaviors where an increase of the delay parameter leads to the persistence of oscillations or more complex dynamics.